A preliminary study of gut microbiome variation and HPA axis reactivity in healthy infants. (February 2021) - Rosin, Samuel; Xia, Kai; Azcarate-Peril, M. Andrea; Carlson, Alexander L.; Propper, Cathi B.; Thompson, Amanda L.; Grewen, Karen; Knickmeyer, Rebecca C.
Highlights: Infants show robust cortisol reactivity to heel stick at 1 month of age. Diversity of gut microbiome associated with cortisol reactivity to heel stick. Associations with specific genera and sample sizes for larger studies explored. Abstract: The Hypothalamic Pituitary Adrenal (HPA) axis regulates hormonal responses to stress in both humans and animals and is dysregulated in a wide range of psychiatric disorders. There is strong evidence from rodent studies that gut microbial composition influences HPA axis development. In humans, variation in the gut microbiome has been associated with several psychological domains including depression and cognitive development, but studies focused on HPA axis development are still lacking. We tested whether differences in microbial composition are associated with HPA axis reactivity in a pilot study of 34 healthy human infants. HPA axis reactivity was assessed by measuring salivary cortisol in samples taken both before and after a heel stick, and 16S rRNA amplicon sequencing was used for identification and relative quantification of bacterial taxa. Subjects' alpha diversity levels showed a moderate positive association with their cortisol reactivity at one month of age. Exploratory genus-level analyses suggest that Staphylococcus, Prevotella, and genera in the order Lachnospiraceae may be related to cortisol reactivity at one month as well. The current study gives support for the endocrine pathway as a potential mediator in the microbiome-gut-brain axis during infancy, and as such provides motivation for future clinical work to support the development of stress-response systems through the manipulation of gut microbes.